PELAKSANAAN PENDIDIKAN KARAKTER DALAM PEMBELAJARAN - Yulia - Citra (Universitas Negeri Padang, 2012)
This research on the background of the background of the implementation of character education lessons in SLB Negeri 2 Padang. The purpose of this study to obtain a picture of the implementation of character education at School 2 Padang Sarai SLB relating to the policies and administration of the school to provide support for the teaching and learning process that contains values ​​such as character, school environment, teachers are able to apply knowledge of PBM which have values ​​of character, competence of teachers in character education, curriculum used, assessment and community support for the implementation of character education. The methodology of this research is descriptive quantitative approach. From the results of the study indicated that the majority of school personnel have not run in the teaching of character education in the State SLB 2 Padang